Zigzag phosphorene nanoribbons: one-dimensional resonant channels in two-dimensional atomic crystals - Páez, Carlos. J.; Bahamon, Dario. A.; Pereira, Ana L. C.; Schulz, Peter. A. (Beilstein Journal of Nanotechnology, 2016)
We theoretically investigate phosphorene zigzag nanoribbons as a platform for constriction engineering. In the presence of a constriction at one of the edges, quantum confinement of edge-protected states reveals conductance peaks, if the edge is uncoupled from the other edge. If the constriction is narrow enough to promote coupling between edges, it gives rise to Fano-like resonances as well as antiresonances in the transmission spectrum. These effects are shown to mimic an atomic chain like behavior in a two dimensional atomic crystal.
Keywords: 2D materials; constrictions; edge states; phosphorene nanoribbons; quantum dots